SOSIALISASI PEMANFAATAN PENGGUNAAN APLIKASI CEGAH STUNTING UNTUK MEMBENTUK GENERASI STUNNING DI KUNCIRAN JAYA, KOTA TANGERANG - Herdiansah, Arief; Ahmad, Shieva Nur Azizah; Wijayanti, Rima Rizqi; Faridi, Faridi (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2025)
The problem of low nutrition in toddlers is a major problem and concern for the Indonesian government. If the government fails to eliminate or is unsuccessful in reducing stunting cases, Indonesia will likely lack many of the nation's next generation who can continue Indonesia's development towards an advanced, just, and prosperous country for all Indonesian people. Accelerating the reduction of stunting, especially toddlers, has been a priority program of the government for the past 5 years, according to the 2020-2024 RPJMN, with a target of reducing stunting cases by 14% by 2024. To support this, the Indonesian government has developed applications that can help the stunning eradication program, including the healthy child application, the e-PPGBM application, e-HDW, and the Sidata application developed by the Tangerang City government. This socialization activity is carried out by delivering seminars or lectures face to face to the community, also discussions and questions and answers sessions related to how we can prevent stunting to achieve a stunning generation and how to utilize the current stunting prevention application. The socialization activity was carried out in August 2024, attended by +/- 50 participants from the Kunciran Jaya sub-district posyandu cadres. In this activity, pre and post tests were conducted to measure the level of understanding of the material presented, and the data showed that 85% of participants understood the information presented.